The Challenge of African Potentials : Conviviality, Informality and Futurity (Book collections on Project MUSE., 2020)
This collection of articles is based on presentations and discussions at the 2018 African Potentials Forum, held in Accra, Ghana. This forum was a part of the African Potentials Project, which aims to clarify the latent problem-solving abilities, ways of thinking, and institutions that have been created, accumulated, unified, and deployed in the everyday experiences of Africans. The notion of Africa's latent power/potential is not related to romanticisation of the traditional knowledge of African society and its institutions as fixed, essentialised 'magic wands'. This notion also raises objections against political dogmas that seek to smoke out and eliminate thought and values originating in Western modernity. The keyword of the Accra Forum was futurity. Africa's future is laden with possibilities, latent power, and potential. It is bright and hopeful but, simultaneously, bleak and thought-provoking. For nascent democracies and economically challenged communities, the value of this potential lies not in its static qualities but in how these qualities can be harnessed and translated into beneficial practical outcomes. As a concept, 'potential' connotes a time to come; a futurity that is full of known and unknown possibilities, challenges, and opportunities.